STUDI EKSPLORASI TENTANG JIWA ENTREPRENEURSHIP DI KALANGAN MAHASISWA - Endang Mulyani (Jurnal Kependidikan, 2004)
Abstract The high entrepreneurship spirit was the greatest capital in creating the field of job that was more and more limited because of this existence of long-term economic crisis. This research was aimed to find out the entrepreneurship spirit of university students according to gender, the school they came from, their parent’s education and job, and their study program. This research would be performed at the Faculty of Social Science, State University of Yogyakarta (UNY). The population of this program was the university students totaled 1,058 persons for the Education of Business World at the Faculty of Social Science, while the sample taken as many as 105 students and its sampling technique used the proportional random sampling. The technique of collecting data used in this research was the technique of questionnaire. The test of validity was performed by using the technique of Part Whole Correlation and the test of its reliability was used the technique of Alpha. The technique of statistical analysis used was descriptive one, t-test, and Analysis of Variance (ANOVA). This research resulted that (1) the entrepreneurship index of the university students for the Education of Business World was included the enough category, (2) the entrepreneurship index of them was higher in male compared with the female, (3) the students came from senior high school and vocational one had the same entrepreneurship index, (4) there was not a difference in the entrepreneurship index of them looked from their parent’s education, (5) there was not a difference in the entrepreneurship index of them looked from their parent’s job, and (6) their study program for the Education of Economic Cooperation had the highest entrepreneurship index, followed by their ones of Study Program for Accounting and the Education of Office Administration. Keywords: Entrepreneurship